2011
DOI: 10.1111/j.1440-1754.2011.02126.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring antibiotic prescribing in hospitalised children in resource‐poor countries: A systematic review

Abstract: Antibiotic resistance represents a significant threat to global health. Widespread exposure to antibiotics drives the development of antibiotic resistance. Little is known about the exposure to antibiotics of hospitalised children, particularly in resource-poor countries where the burden of infectious disease is highest. The review sought to identify original research quantifying antibiotic use in hospitalised children in resource countries. The methods used were: A systematic search of the MEDLINE, CINAHL, EM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Previous systematic reviews were conducted to explore the effectiveness of interventions to reduce irrational antibiotic prescription in adults and children with various diseases 4 5 8 22–25. The advantages of our review over others are that we focus on a specific population (children) and condition (URI) and stratified analyses according to the type of intervention, which enriched the existing literature as most of the previous studies were descriptive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous systematic reviews were conducted to explore the effectiveness of interventions to reduce irrational antibiotic prescription in adults and children with various diseases 4 5 8 22–25. The advantages of our review over others are that we focus on a specific population (children) and condition (URI) and stratified analyses according to the type of intervention, which enriched the existing literature as most of the previous studies were descriptive.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, prescribing antibiotics for childhood URIs is highly prevalent 4. Antibiotic resistance is frequently observed in young children and more invasive infections occur in this vulnerable population 5. In Asia, every 2 min a child aged under 5 years dies from antibiotic-resistant infections 6…”
Section: Introductionmentioning
confidence: 99%
“…Similar assessments of CDSS impact on overall antimicrobial consumption in our hospital has been limited by a lack of feasible and widely accepted measures to monitor use in paediatrics . Unlike adult hospitals without electronic prescribing or administration records, there is no paediatric equivalent for the World Health Organization's defined daily dose for adults . As a result, the CDSS is often used by the local AMS to monitor antimicrobial use.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of the available literature by Irwin and Sharland identified eighteen studies and revealed high exposure of hospitalised children to antibiotics [9]. Naughton et al compared PPS data from four regional/general hospitals in Ireland and identified 29% to 37% of paediatric and neonatal patients on antibiotics.…”
Section: Discussionmentioning
confidence: 99%